The pathophysiological spectrum of maternal complications of pregnancy-induced hypertension: Review Article - Adedeji Okikiade; Chidinma Kanu; Oluwadamilare Iyapo; Ololade Omitogun (Medical Laboratory Journal)
Background: Pregnancy-induced hypertension (PIH) is a multi-system disorder affecting 6-8% of pregnancies in the U.S. and contributing significantly to maternal mortality, accounting for 16% in developed countries. It progresses from preeclampsia to eclampsia, leading to multi-organ damage through mechanisms such as oxidative stress, placental ischemia, and endothelial dysfunction. While the exact pathogenesis remains unclear, genetic, immunologic, and environmental factors are implicated. The American College of Obstetricians and Gynecology (ACOG) recommends initiating treatment when diastolic blood pressure exceeds 105-110 mmHg. Methods: This narrative review examines existing literature on PIH, including epidemiological data, pathophysiological mechanisms, clinical management guidelines, and associated complications such as abnormal placentation, oxidative stress, and endothelial dysfunction. Results: This study demonstrates that hypertensive disorders of pregnancy (HDP) significantly impact maternal and fetal health, particularly in developing countries with limited healthcare access. Early detection and continuous monitoring play a key role in reducing complications. Additionally, HDP is associated with increased long-term cardiovascular and metabolic risks, highlighting the importance of postpartum follow-up. Conclusion: HDP poses a serious threat to maternal and fetal health, with potential long-term consequences. Effective management requires early diagnosis, close monitoring, and postpartum follow-up. Global implementation of risk assessment and targeted care strategies can help reduce the burden of this condition. Strengthening healthcare systems and increasing awareness among healthcare providers and patients are essential steps toward improving outcomes.